Value Added Tax and Vat Flat Rate Scheme in Ghana, Any Cascading Implications - Obeng, George (Asian Development Policy Review, 2018)
Ghana in 2017 introduced a new VAT flat rate scheme (VFRS) of 3% for retailers as against the existing normal rate of 17.5%. Debate, similar to that VAT, as to the tax incidence and the cascading effect on businesses in the distribution chain ensued. The Revenue Authority and retail businesses are content that VFRS will mitigate the tax burden of consumers and simplify its calculation. Other business houses posit that the tax is upon tax with cascading effect on prices. Literature comparing charges of VAT and VFRS on a product in distribution is limited. Literature is reviewed with models testing any cascading effect of VFRS on consumers and the effect on tax revenue. The paper concludes that the incidence of VAT is on the consumer with no cascading effect. VFRS is charged onto the final consumer of the product. VFRS can mitigate the tax burden on consumers’ dependant on the market orientation, type of industry and business environment. Government can use VFRS to stabilize the economic environment in the event of market failure for tax optimality. The paper will enhance policy on optimizing tax revenue with different tax rates at different production sectors of the economy.